Comparison of Engine Performance and Emissions for Petroleum Diesel Fuel, Yellow Grease Biodiesel, and Soybean Oil Biodiesel - Canakci, M; Van Gerpen, J.H (Transactions of the ASAE, 2003)
Biodiesel is a non-toxic, biodegradable and renewable alternative fuel that can be used with little or no engine modifications. Biodiesel is currently expensive but would be more cost effective if it could be produced from low-cost oils (restaurant waste, frying oils, animal fats). These low-cost feedstocks are more challenging to process because they contain high levels of free fatty acids. A process for converting these feedstocks to fuel-grade biodiesel has been developed and described previously. The objective of this study was to investigate the effect of the biodiesel produced from high free fatty acid feedstocks on engine performance and emissions. Two different biodiesels were prepared from animal fat-based yellow grease with 9% free fatty acids and from soybean oil. The neat fuels and their 20% blends with No. 2 diesel fuel were studied at steady-state engine operating conditions in a four-cylinder turbocharged diesel engine. Although both biodiesel fuels provided significant reductions in particulates, carbon monoxide, and unburned hydrocarbons, the oxides of nitrogen increased by 11% and 13% for the yellow grease methyl ester and soybean oil methyl ester, respectively. The conversion of the biodiesel fuel's energy to work was equal to that from diesel fuel.